2022
DOI: 10.4070/kcj.2021.0269
|View full text |Cite
|
Sign up to set email alerts
|

Causal Association Between Alcohol Consumption and Atrial Fibrillation: A Mendelian Randomization Study

Abstract: Author's summary Previous observational studies presented a positive association between alcohol and atrial fibrillation (AF). However, previous studies using genetic polymorphisms on the causal relationship between alcohol consumption and AF have reported conflicting results. This study evaluated the causality between alcohol consumption and AF using the aldehyde dehydrogenase 2 ( ALDH2 ) rs671 polymorphism. In 8,964 cohort participants, genetic analysis and Mendelian randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In addition, ALDH2 * 2/ * 2 with non-drinking was discovered to be a protective factor for AF. As supported in our study, Yamashita T et (25).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, ALDH2 * 2/ * 2 with non-drinking was discovered to be a protective factor for AF. As supported in our study, Yamashita T et (25).…”
Section: Discussionsupporting
confidence: 89%
“…These participants even had a reduced risk of AF compared to wild-type non-drinkers [ 228 ]. A Korean Mendelian randomization study with 8964 participants using the ALDH2 genotypes reported a significant relationship between alcohol consumption and AF [ 229 ].…”
Section: Atrial Myocardium and Alcoholmentioning
confidence: 99%
“…They observed that genetically predicted alcohol consumption was significantly associated with AF, suggesting that alcohol may be causally associated with AF development. 6) This study also has limitations. There is the possibility of misclassification in measuring the intake of alcohol and the presence of AF.…”
mentioning
confidence: 91%
“…In this issue of Korean Circulation Journal , Yang et al 6) adds new evidence for a relationship between alcohol and AF. This makes an important contribution to understanding the impact of alcohol on the risk of AF.…”
mentioning
confidence: 99%
See 1 more Smart Citation